2019
DOI: 10.1371/journal.pntd.0006805
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic profiling of ticks: Identification of novel rickettsial genomes and detection of tick-borne canine parvovirus

Abstract: BackgroundAcross the world, ticks act as vectors of human and animal pathogens. Ticks rely on bacterial endosymbionts, which often share close and complex evolutionary links with tick-borne pathogens. As the prevalence, diversity and virulence potential of tick-borne agents remain poorly understood, there is a pressing need for microbial surveillance of ticks as potential disease vectors.Methodology/Principal FindingsWe developed a two-stage protocol that includes 16S-amplicon screening of pooled samples of ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 65 publications
1
15
1
Order By: Relevance
“…Enterobacteriaceae was the most abundant bacterial family in R. microplus ticks collected from cattle whereas Rickettsiaceae, Oxalobacteraceae, and Micrococcaceae were abundant in the R. turanicus ticks infesting goats 41 . Furthermore, the results of this study differ from Ravi et al 60 who reported four www.nature.com/scientificreports/ bacterial families: Coxiellaceae, Francisellaceae, Rickettsiaceae and Anaplasmataceae in H. dromedarii, Rhipicephalus sanguineus and Haemaphysalis concinna. The differences among families could be attributed to host specific factors.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Enterobacteriaceae was the most abundant bacterial family in R. microplus ticks collected from cattle whereas Rickettsiaceae, Oxalobacteraceae, and Micrococcaceae were abundant in the R. turanicus ticks infesting goats 41 . Furthermore, the results of this study differ from Ravi et al 60 who reported four www.nature.com/scientificreports/ bacterial families: Coxiellaceae, Francisellaceae, Rickettsiaceae and Anaplasmataceae in H. dromedarii, Rhipicephalus sanguineus and Haemaphysalis concinna. The differences among families could be attributed to host specific factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, the genus level identifications presented in the current study are provided as preliminary baseline data, which may require further confirmation. Our results indicated that Acinetobacter and Corynebacterium were the two most abundant genera detected in the microbiota of H. dromedarii from all locations with high sequence ratios 47 and Saudi Arabia 48 . We found significant associations between Acinetobacter, Escherichia and Francisella and between these three genera and several other genera.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…It is reassuring that targeted metagenomics sequencing of the >13,000 samples that they had found as many or more of each species, but still unknown if any of the Borrelia-specific PCR positive samples were not able to be detected by targeted metagenomics. shown to work in principal to identify pathogens transmitted by ticks both from human specimens (12,13) as well as direct testing of ticks (14,15). However, the lack of a targeted sequence requires substantially more sequencing depth and interpretation of data can be much more challenging.…”
mentioning
confidence: 99%